중앙공무원과 지방공무원의 보상 인식과 직무만족이 성과에 미치는 영향에 관한 비교 연구: 성과관리와 조직공정성의 조절효과를 중심으로 - 구주영; Koo Jooyoung (공공정책연구, 2021)
본 연구에서는 중앙 및 지방공무원의 조직 및 인사관리, 성과관리 그리고 조직행태적 요인을 비교 분석하였다. 이와 같은 점을 감안 했을 때, 본 연구는 중앙 정부와 지방 정부간 관료제에 대한 비교 연구이고, 정부간 성과관리 역량의 비교 연구이며, 소속 유형에 따른 공무원 행태에 대한 비교 연구이다. 이러한 비교를 위해 본 연구에서는 성과관리와 조직공정성에 대한 공무원의 인식에 따라, 보수 및 직무만족 요인이 성과에 미치는 영향을 어떻게 변화되는지 분석하였다. 분석결과를 살펴보면, 보수는 중앙 및 지방정부 모두 업무 및 조직성과에 부정적인 영향을 미치고 있었지만, 직무만족은 긍정적인 영향을 미치고 있었다. 하지만 성과관리와 조직공정성 변수는 중앙 및 지방공무원 여부에 따라 상반된 결과가 도출되었다. 중앙공무원의 경우, 보수가 업무 및 조직성과에 미치는 영향을 성과관리가 강화시켜주고 있었다. 또한, 직무만족이 업무성과에 미치는 긍정적인 영향을 성과관리가 감소시키고 있었다. 반면 지방공무원의 경우, 직무만족이 업무성과에 미치는 긍정적인 영향을 성과관리가 강화시켜 주고 있다는 점을 확인할 수 있었다. 이에 더하여, 조직공정성은 중앙공무원의 보수와 업무성과간 관계와 마찬가지로, 보수가 업무성과에 미치는 긍정적인 영향을 조직공정성 인식이 강화시켜주고 있었으며, 직무만족이 업무성과에 미치는 긍정적인 영향을 감소시키고 있는 것으로 분석되었다. 이와는 반대로, 지방공무원의 직무만족이 업무성과에 미치는 긍정적인 영향을 조직공정성이 강화시키고 있는 것으로 확인되었다. 분석결과를 고려할 때, 공무원의 조직, 인사 그리고 성과관리는 중앙 및 지방정부의 보상체계, 직무운영체계가 연계될 수 있도록, 공공관리자와 담당부서의 전략적인 관리가 수반되어야 한다는 점을 확인할 수 있었다. In this study, the organization and management of, the performance management of, and organizational behavioral factors related to national and local public officials were compared and analyzed. This study compared national and local bureaucracies, central and local governments’ performance management capabilities, and civil servants’ behaviors by their affiliation. These comparisons were conducted by analyzing how public officials’ remuneration and job satisfaction affected their job performance according to their perceptions of performance management and organizational fairness. Analysis results showed that both national and local governments negatively affected public officals’ work and organizational performance while job satisfaction positively affected them. However, performance management and organizational fairness produced different results for national and local officials. Performance management strengthened the impact of remuneration on national government officials’ work and organizational performance. In addition, performance management reduced the strength of the positive impact of job satisfaction on job performance. For local officials, performance management is strengthened the positive impact of job satisfaction on work performance. In addition, organizational fairness strengthened the positive impact of awareness of organizational fairness and reduced the positive impact of job satisfaction on work performance for national public officials. However, organizational fairness strengthened the positive impact of local public officials’ job satisfaction on their work performance. These results indicate that the organization, personnel management, and performance management of public officials should be accompanied by strategic management to link national and local governments’ compensation systems.